Determinan Optimalisasi Pemanfaatan Aset Daerah Di Kota Yogyakarta - Maulida Annisa; Rifki Khoirudin (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this research is to see and examine whether asset inventory, legal audit, asset valuation, as well as supervision and control can affect the optimization of the utilization of regional assets in the city of Yogyakarta. The population in this study were employees of the Yogyakarta City BPKAD. The research sample was taken using non-probability sampling, namely purpose sampling with a total of 105 respondents. The type of research data is qualitative data. Sources of data using primary data, by distributing questionnaires to respondents. Primary data sources are employees of the Yogyakarta City BPKAD. Data collection techniques were carried out by researchers using field research techniques, by distributing questionnaires. The results of the t-test state that the coefficient of the asset inventory variable has a positive and significant effect on the optimization of regional asset utilization variables. The legal audit variable shows a negative and insignificant direction towards optimizing the utilization of regional assets. Asset valuation has a negative and significant direction towards optimizing the utilization of regional assets. Supervision and control variables have a negative and insignificant effect on the optimization of regional asset utilization variables. In this study, only asset inventory variables have a positive effect on optimizing the utilization of regional assets in the city of Yogyakarta.